Exploring the basic concepts of Calculus through a case study on motion in gravitational space - Tekeli, Miklós; Karsai, János; Kopasz, Katalin (Teaching Mathematics and Computer Science, 2024)
In universities, the Calculus course presents significant challenges year after year. In this article, we will demonstrate how to use methods of Realistic Mathematics Education (RME) to introduce the concepts of limits, differentiation, and integration based on high school kinematics and dynamics knowledge. All mathematical concepts are coherently built upon experiences, experiments, and fundamental dynamics knowledge related to motion in a gravitational field. With the help of worksheets created using GeoGebra or Microsoft Excel, students can conduct digital experiments and later independently visualize and relate abstract concepts to practical applications, thereby facilitating their understanding. Subject Classification: 97D40, 97I40, 97M50